Comparative efficacy of fixed dose combination of brinzolamide 1% and timolol 0.5% without versus with benzalkonium chloride following single ocular instillation in New Zealand white rabbits - Vakharia, Monali; Pateliya, Bharat; Ghose, Sukhendu Bikash; Burade, Vinod; Rohira, Poonam (International Journal of Basic & Clinical Pharmacology, 2023)
Background: Benzalkonium chloride (BAK) is the most used preservative in topical ophthalmic formulations. BAK causes dry eye and trabecular meshwork degeneration. Hence, BAK-free formulations are desirable for chronic conditions like glaucoma. The objective of this study was to compare the efficacy of BAK-free versus BAK-containing ophthalmic suspension of fixed dose combination (FDC) of brinzolamide and timolol on their intraocular pressure (IOP) lowering effect following a single ocular instillation in New Zealand White (NZW) rabbits. Methods: Twelve normotensive NZW rabbits (male) between 9-12 months of age (3.4-4.4 kg) received a single ocular instillation (35 ml) in left eye of either ophthalmic suspension containing FDC of brinzolamide (1% w/v)/timolol (0.5% w/v) without BAK (n=6, test) or with BAK 0.01% w/v (n=6, reference). IOP was measured before ocular instillation (baseline) and at 2, 4, 6, 8 and 24 hours after instillation using a pneumatonometer. Change in IOP from baseline were calculated and analysed using repeated measures analysis of variance (ANOVA) followed by Bonferroni post-test for pairwise comparisons. Results: Significant IOP reduction (p<0.05) from baseline was seen in both test and reference groups, up to 6 hours after instillation. Maximum IOP reduction was 25.5% and 22.6% at 2 hours in the test and reference group respectively. No significant differences (p>0.05) were observed between the test and reference group for the change in IOP at all time points. Conclusions: BAK-free and BAK-containing ophthalmic suspension of FDC of brinzolamide 1% and timolol 0.5% after a single ocular instillation in normotensive NZW rabbits produces similar reductions in IOP.